دراسة تأثير الزّمن الميّت في عداد غايغر – موللر على الظاهرة الفيزيائيّة المدروسة (Latakia University Journal -Basic Sciences Series, 2016)
تمَّ في هذا البحث دراسة ميّزات وصفات عدّاد غايغر-موللر، أي معايرة هذا العدَّاد: تحديد نقطة عمل العدّاد بيانياً، وَوُجد أنّها تقع بين الـ 360 فولطاً والـ 600 فولط، أي أنّ نقطة العمل هي . وتكون عادةً المنطقة بين  و  أقل من 300 فولط، في هذا البحث 240 فولطاً. تمَّ أيضاً تحديد ميل هضبة العدّاد من أجل تغير قدره 100 فولط كنسبة مئوية، فوجد أنّ القيمة الوسطى للميل (ميل الهضبة) . وُجد أنّ الزّمن الميّت لعدّاد غايغر-موللر يساوي: . يعني هذا أنّ "العدّ الحقيقي" يختلف عن "العدّ المُقاس" (التجريبي)، ويصبح للزّمن الميّت تأثيرٌ كبيرٌ في حالة المنابع المشعة ذات النشاط الإشعاعي الكبير. In this paper, we study the features and properties of Geiger-Mueller counter: calibration Geiger-Mueller counter, determining the voltage plateau for the Geiger tube and to establish a reasonable operating point for the tube. We find that the operating point is locating between 360 Volts and 600 Volts that mean the value of this point is 480 Volts. And the region between V1 and V2 less than 300 Volts, in this research 240 Volts. We have determined the slope of the plateau in the graph for variation about 100 Volts. It found that the average value of the slope is less than 2,67%. It isfound that dead time of Geiger-Mueller is: .This means that the “true counting” is differ from "measuredcounting" (experimental value). The dead time will have a great influence in the case of high radiation sources.